Pre-service Teacher Education Rethinking the Engagement with Schools in the Two-year B.Ed. Programme - Kohli, Jyoti (JOURNAL OF INDIAN EDUCATION, 2017)
This paper is a reflective piece on enhancing the pre-service teachers’ engagement with schools, which, it is argued, will help them arrive at a comprehensive understanding of the school system while developing connections between theory and practice. It is proposed that this requires the pre-service teacher education institutions to re-envision the school observation and school internship programmes spread over two years of the B.Ed. curriculum in order to ensure that teachers entering the school system are ready for the myriad demands they are likely to face in schools.